Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus terhadap Belanja Modal Propinsi Jawa Barat - Rina Nofiyanti; Novita Sulistyowati; Athaya Salsabila; Diana Sari (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2026)
The execution of regional autonomy in Indonesia does not abolish the central government's duty to consistently provide transfers of balancing funds aimed at achieving financial equilibrium between the central and regional administrations and focusing the objectives of regional autonomy. This study seeks to assess the effect of Regional Tax/RT, Regional Levy/RL, General Allocation Funds/GAF, and Special Allocation Funds/SAF on Capital Expenditures/CE in the province of West Java. The research method uses a quantitative approach with the independent variables being RT, RL, GAF and SAF and the independent variable being CE. The sampling approach utilized is saturated sampling, encompassing 27 regencies/cities within West Java province, which includes 18 regencies and 9 cities, using time series data over 4 years, specifically from 2018 to 2021. The analytical method applied is multiple linear regression, with a total data consisting of 108. The findings indicate that both RT and GAF significantly impact CE, meanwhile RL and SAF do not have a notable effect on CE. Simultaneously, all variables independent affect Capital Expendiures.